A Systematic Literature Review on Digital Storytelling Authoring Tool in Education: January 2010 to January 2020. Issue 9 (28th May 2022) - Quah, Chia Yi; Ng, Kher Hui
ABSTRACT: While early research in digital storytelling was primarily based on a mixture of digital media, the last 10 years has seen a rapid increase in the use of advanced technologies such as augmented reality (AR), wearable, tangible, and mobile devices. Although a proliferation of digital storytelling authoring tools has been introduced to improve learning, there is a lack of systematic review to inform how it has been designed and developed as well as implemented in education. This paper presents a systematic review of 91 studies highlighting the technology and use trends related to authoring tools in educational digital storytelling. Our analysis identifies best practices in designing the authoring tools, synthesized as design guidelines for future researchers and practitioners in the field. Possible challenges of incorporating the tools in the classroom are explored, and directions for future design and development of similar tools are suggested.